Autologous and Nonautologous Blood Transfusion in Patients with Ruptured Ectopic Pregnancy and Severe Blood Loss - Huang, Jingxian (Biomed Res Int, 2017)
BACKGROUND: There are some theoretical concerns for the use of intraoperative cell salvage (ICS) in patients with ectopic pregnancy. This study aimed to observe the impact of ICS on the coagulation function and clinical outcomes of patients with ruptured ectopic pregnancy and severe blood loss. METHODS: This was a retrospective study of 225 patients with ruptured ectopic pregnancy and severe blood loss treated at the Third Affiliated Hospital of Guangxi Medical University between January 2012 and May 2016. Patients were grouped according to ICS (n = 116) and controls (n = 109, allogenic transfusion and no transfusion). RESULTS: Compared with controls, patients with ICS had shorter hospitalization (P = 0.007), lower requirement for allogenic blood products (P < 0.001), and higher hemoglobin levels at discharge (P < 0.001). There were no complications/ adverse reactions. In the ICS group, hemoglobin at discharge (−6.5%, P = 0.002) and thrombin time (−3.7%, P = 0.002) were decreased 24 h after surgery, while 24 h APTT was increased (+4.6%, P < 0.001). In the control group, hemoglobin at discharge (−16.8%, P < 0.001) was decreased after surgery and 24 h APTT was increased (+2.4%, P = 0.045). At discharge, hemoglobin levels were higher in the ICS group (P < 0.001). CONCLUSION: ICS was associated with good clinical outcomes in patients with ruptured ectopic pregnancy and severe blood loss.